Epoxy–Silica Functionally Graded Materials: A Review - AbdulRazaq, Jaafar Shareef; Hasan, Abdul Kareem F. Hassan; Nuha Hadi Jasim Al (Basrah Journal for Engineering Sciences, 2023)
This article provides an overview of the studies that have been conducted on the characteristics of epoxy resins containing various types of silica nanoparticles and microparticles, as well as their performance in the industrial application of functionally graded materials (FGMs). Silica nanoparticles and microparticles are used to create epoxy resins in order to improve various properties, such as thermal stability, adhesiveness, electrical conductivity, strength, modulus, and toughness. This review examines the literature that has been published in the last decade, compares the results, focuses on the mechanical and thermal properties, and discusses the changes that have resulted in improvements in those properties. Previous experimental findings are presented and contrasted to demonstrate the extent to which silica filler content contributes to improving the properties of composite materials. The findings reveal that the characteristics of epoxy compounds can be improved by adding a particular amount of silica particles. There is a correlation between an increase in the silica amount and an increase in the Young modulus of epoxy compounds, this correlation becomes stronger as the silica amount increases. Additionally, the tensile strength of epoxy compounds increases to a certain limit as the amount of silica nanoparticles increases. In contrast, the hardness of the material increases as the silica amount increases. The density of the material also increases steadily as the silica amount in the material increases. According to thermal analysis results from calorimetric research on epoxy–silica systems, the glass transition temperature increases as the silica amount increases.